Ecologies of security: On the everyday security tactics of female sex workers in Nairobi, Kenya. Issue 12 (2nd December 2018) - Lorway, Robert; Lazarus, Lisa; Chevrier, Claudyne; Khan, Shamshad; Musyoki, Helgar K.; Mathenge, John; Mwangi, Peninah; Macharia, Pascal; Bhattacharjee, Parinita; Isac, Shajy; Kimani, Joshua; Gaaki, Gloria; et al.
ABSTRACT: This paper highlights important environmental dimensions of HIV vulnerability by describing how the sex trade operates in Nairobi, Kenya. Although sex workers there encounter various forms of violence and harassment, as do sex workers globally, we highlight how they do not merely fall victim to a set of environmental risks but also act upon their social environment, thereby remaking it, as they strive to protect their health and financial interests. In so doing, we illustrate the mutual constitution of 'agency' and 'structure' in social network formations that take shape in everyday lived spaces. Our findings point to the need to expand the focus of interventions to consider local ecologies of security in order to place the local knowledges, tactics, and capacities that communities might already possess on centre stage in interventions. Planning, implementing, and monitoring interventions with a consideration of these ecologies would tie interventions not only to the risk reduction goals of global public health policy, but also to the very real and grounded financial priorities of what it means to try to safely earn a living through sex work.